The Differentiated Teaching Module Development to Realize Pancasila Student Profile on the Sekolah Penggerak Curriculum - Ndiung, Sabina; Jediut, Mariana; Nendi, Fransiskus (Universitas Pendidikan Ganesha, 2023)
The aims of this research is to develop teaching modules that promote critical and creative thinking profile. This study involved six principals and 18 teachers from East Manggarai Regency. A questionnaire technique was used to obtain data. Expert validation on content, grammar, and design. The findings revealed that 83.33 % of principals and instructors at sekolah penggerak required differentiated teaching modules, with 91.7 %. Meanwhile, the HOTS-oriented assessment aspect, 83.33 %, and the level of development urgency, 95.83 %. It is concluded that the development of differentiated teaching modules is required in assisting elementary teachers for managing student-centered learning.